Modeling of the formation of triple complexes of the essential trace element iron with riboflavin and essential amino acids - A. V. Blinov; A. A. Gvozdenko; A. B. Golik; M. A. Kolodkin; M. A. Pirogov (Современная наука и инновации, 2023)
In this work, we simulated the process of formation of triple complexes of the essential trace element iron with riboflavin and essential amino acids. The simulation was carried out in the QChem software using the IQmol molecular editor. To begin with, the modeling of the molecules of essential amino acids was carried out: L-valine, L-leucine, L-isoleucine, Lmethionine, L-threonine, L-lysine, L-phenylalanine and L-tryptophan. Modeling was carried out by the interaction of the iron atom with various pairs of nitrogen heteroatom and enol oxygen of riboflavin, as well as with the carboxyl group and α-amino group of the amino acid. As a result, it was found that the interaction of the trace element iron with riboflavin and essential amino acids is energetically favorable (∆E > 2575 kcal/mol) and chemically stable (0.075 ≤ η ≤ 0.138 eV). Based on the data obtained, the most probable configuration of the molecular complex was determined - interaction with riboflavin through N5 in the pyrazine ring and enol oxygen attached to the C4 atom in the pyrimidine ring of riboflavin. The molecular system that has the highest difference in total energy (∆E = 2577.501) and chemical hardness (η = 0.138 eV), and therefore the most energetically favorable and chemically stable, is the copper valinatoriboflavinate molecular complex, in which the interaction of iron with riboflavin occurs through N5 in the pyrazine ring and enol oxygen attached to the C4 atom in the pyrimidine ring riboflavin.